A Comparison in Mechanical Properties of Cermets of Calcium Silicate with Ti-55Ni and Ti-6Al-4V Alloys for Hard Tissues Replacement - Azim Ataollahi Oshkour; Sumit Pramanik; Seyed Farid Seyed Shirazi; Mehdi Mehrali; Yat-Huang Yau; Noor Azuan Abu Osman (The Scientific World Journal)
This study investigated the impact of calcium silicate (CS) content on composition, compressive mechanical properties, and hardness of CS cermets with Ti-55Ni and Ti-6Al-4V alloys sintered at 1200°C. The powder metallurgy route was exploited to prepare the cermets. New phases of materials of Ni16Ti6Si7, CaTiO3, and Ni31Si12 appeared in cermet of Ti-55Ni with CS and in cermet of Ti-6Al-4V with CS, the new phases Ti5Si3, Ti2O, and CaTiO3, which were emerged during sintering at different CS content (wt%). The minimum shrinkage and density were observed in both groups of cermets for the 50 and 100 wt% CS content, respectively. The cermets with 40 wt% of CS had minimum compressive Young’s modulus. The minimum of compressive strength and strain percentage at maximum load were revealed in cermets with 50 and 40 wt% of CS with Ti-55Ni and Ti-6Al-4V cermets, respectively. The cermets with 80 and 90 wt% of CS showed more plasticity than the pure CS. It concluded that the composition and mechanical properties of sintered cermets of Ti-55Ni and Ti-6Al-4V with CS significantly depend on the CS content in raw cermet materials. Thus, the different mechanical properties of the cermets can be used as potential materials for different hard tissues replacements.